Autores velados e revelados: uma análise do discurso de alunos de letras - Barros, Luciana Borges Alves Pinto e (2006)
This paper presents the construction of a possible trajectory in the constitution of authorship by three students from the CAJ Modern Language course. To tread along the route of this reconstitution came from the analysis of these students essays, done in their last university year, as an obligatory inquiry in the Portuguese Teaching subject. The Modern Language student, who is about to graduate, seen in this work as a subjectauthor, is a reader who happens to read themselves, assuming texts in order to compose others. We know that writing exists after the subject s reading, who wishes a unique view and, from this point, they (re)construct it from the first reproduction. In this manner, authorship is viewed in this study as a single process, with the presence of the Other that allows the (un)veiling process in a non-organized and unpredictable way inside of the subject-constructor of their own authorship. To analyse students discourses in their essays shows how singularity occurs truly and goes beyond the ready and used concept of students education: after all, they educate themselves based on their own manners and with their Others, and all the time.